'Am I mad?': the Windham case and Victorian resistance to psychiatry. Issue 4 (December 2019) - Degerman, Dan
This article revisits the notorious trial of William Windham, a wealthy young man accused of lunacy. The trial in 1861–2 saw the country's foremost experts on psychological medicine very publicly debate the concepts, symptoms and diagnosis of insanity. I begin by surveying the trial and the testimonies of medical experts. Their disparate assessments of Windham evoked heated reactions in the press and Parliament; these reactions are the focus of the second section. I then proceed to examine criticism of psychiatry in the newspapers more generally in the 1860s, outlining the political resistance to psychiatry and the responses of some leading psychiatrists. In conclusion, I consider what this says about the politics of medicalization at the time.